How to Approach to Torsional Adnexal Mass in a Geriatric Age Woman: A Case Report and Literature Review - ERİN, Recep; TEKİN, Yeşim BAYOĞLU; KOÇAK, Fatma Gülgün (International Journal of Innovative Research in Medical Science, 2019)
We aimed to present how to approach to the postmenopausal torsional adnexal masses, accompanied by a case report and literature review. A 90 year-old geriatric age woman with G5P5 admitted to emergency department with complaints of nausea, vomiting and abdominal pain. We detected a tumoral mass with solid component and irregular surface suspected malignancy in the midline of the pelvis. Laparotomy was performed due to the suspicion of torsion and malignancy. We detected a approximately 25 cm torsional blue-purple colored tumoral mass originating from the right ovary and performed total abdominal hysterectomy and bilateral salpingo-oferectomy. Pathology was reported as a sex cord stromal tumor with torsional. The patient was discharged with complete recovery on the 3rd postoperative day. Adnexal torsion is a gynecologic emergency. It should be considered in postmenopausal women who present with abdominal pain and adnexal mass.